Adjectival definiteness marking in Lithuanian – one more puzzle piece: Qualitative adjectives that could but do not take definite forms - Trakymaitė, Ringailė (Baltistica, 2021)
This data-driven paper adds to the broader discussion on adjectival definiteness marking and, more specifically, definiteness marking in Lithuanian by providing some insights into why a large group of qualitative adjectives that could, in principle, derive definite (long) forms rarely do so in practice. This group of adjectives is not homogenous but could be divided into a number of rather clearly defined sub-groups, based on semantic-pragmatic factors or on functions performed in the NP/sentence. It will be argued that the inability to establish a category (both taxonomic or ad hoc), and hence to assume a morphological definiteness marker, occurs for two reasons: 1) a property denoted by the adjective does not meet the semantic-pragmatic requirements needed for the underlying category; 2) the adjective denotes not a property, but rather something else, e.g., quantification, possession, similarity, ordinal relations, specificity or similar.